The Righteousness of God in Psalms and Romans - Turner, Geoffrey (Scottish journal of theology, 2010)
Paul quoted extensively from scripture, especially in Romans. Many of these citations are from the Psalms, using the Septuagint. Paul could have found all his vocabulary and concepts for ‘justification by faith’ in the Psalms. The Psalms contain a doctrine of ‘righteousness through faithfulness’: God is righteous by forming a covenant with Israel, and proves his righteousness by remaining faithful to that covenant despite Israel's failings. He will remain faithful to the end by vindicating his righteous ones when they are oppressed by the ungodly. Israelites are righteous by having been elected to the covenant and will remain righteous through faithfulness to God, the marks of which are the avoidance of idolatry and keeping the law. Far from rejecting this Old Testament inheritance, Paul takes over this doctrine of ‘righteousness through faithfulness’ as it stands in the Psalms (Romans 1:18–3:20) and then christologises it (from 3:21). The mark of faithfulness to God now is no longer the law, however, but faithfulness to Christ, who is himself the model of faithfulness and what it is to be righteous. This understanding of how one becomes righteous is located by Paul himself within his fivefold scheme of salvation at Romans 8:30: foreknown, predestined, called, made righteous and glorified.